2003
DOI: 10.2169/internalmedicine.42.517
|View full text |Cite
|
Sign up to set email alerts
|

Fulminating Onset Type 1 Diabetes with Positivity for Anti-GAD Antibody and Elevated Pancreatic Exocrine Enzyme Concentrations

Abstract: A 52-year-old man was admitted to our hospital for diabetic ketoacidosis. On admission, HbAic was 6.5%, anti-GAD antibody 10.3 U/ml, serum amylase 144 IU//, lipase 169 XJ/l and elastase-1 1,000 ng/dl. There were no abdominal symptoms, and abdominal CT showed unremarkable findings. He was treated with intensive insulin therapy. After 1 month, urinary excretion of C-peptide was 3.8 jig/day. Serum pancreatic exocrine enzyme concentrations returned to normal after 3 months. After 10 months, anti-GAD antibody had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, high serum pancreatic enzyme levels cannot rule out the presence of autoimmune type 1 diabetes, as it has been shown that 10% of newly diagnosed type 1 diabetic patients in Belgium and a Japanese patient diagnosed with fulminant-onset type 1 diabetes had elevated pancreatic exocrine enzyme concentrations along with clear signs of autoimmune abnormalities (i.e., GAD autoantibodies, etc.) (21,22).…”
Section: Type 1 Diabetes: a Chronic Inflammatory Disease Of The Isletsmentioning
confidence: 99%
“…However, high serum pancreatic enzyme levels cannot rule out the presence of autoimmune type 1 diabetes, as it has been shown that 10% of newly diagnosed type 1 diabetic patients in Belgium and a Japanese patient diagnosed with fulminant-onset type 1 diabetes had elevated pancreatic exocrine enzyme concentrations along with clear signs of autoimmune abnormalities (i.e., GAD autoantibodies, etc.) (21,22).…”
Section: Type 1 Diabetes: a Chronic Inflammatory Disease Of The Isletsmentioning
confidence: 99%
“…here we report a 63-year-old case of abrupt onset autoimmune type 1 diabetes, mimicking FT1DM. in addition to the above mentioned two autoimmune cases [6,7], the present case draws an attention in terms of differential diagnosis between typical FT1DM and this rapidly progressive form of autoimmune type 1 diabetes. …”
mentioning
confidence: 76%
“…although FT1DM is basically classified into type 1B diabetes as indicated by absence of islet-related autoantibodies, two atypical cases showing the mixed characteristics of FT1DM and autoimmune type 1 diabetes (i.e. anti-GaD antibody positivity) have been reported [6,7].…”
mentioning
confidence: 99%
“…Several reports have remarkably demonstrated cases of the onset of fulminant type 1 diabetes with a presence of GAD Ab during ICI therapy. 4 , 11 , 12 , 13 Previous reports suggest that the destruction of β-cells due to ICI therapy could cause a rapid release of the intracellular GAD antigen with the consequent development of GAD Abs. 14 , 15 Alternatively, there is insufficient evidence to conclude that the presence of GAD Abs at baseline is a risk factor for type 1 diabetes in patients treated with ICI therapy.…”
Section: Discussionmentioning
confidence: 99%